Dopamine D1 Receptor in the Nucleus Accumbens Modulates the Emergence from Propofol Anesthesia in Rat - Zhang, Yi; Gui, Huan; Duan, Zikun; Yu, Tian; Zhang, Jie; Liang, Xiaoli; Liu, Chengxi (Neurochemical research, 2021)
It has been reported that systemic activation of D1 receptors promotes emergence from isoflurane-induced unconsciousness, suggesting that the central dopaminergic system is involved in the process of recovering from general anesthesia. The nucleus accumbens (NAc) contains abundant GABAergic medium spiny neurons (MSNs) expressing the D1 receptor (D1R), which plays a key role in sleep–wake behavior. However, the role of NAc D1 receptors in the process of emergence from general anesthesia has not been identified. Here, using real-time in vivo fiber photometry, we found that neuronal activity in the NAc was markedly disinhibited during recovery from propofol anesthesia. Subsequently, microinjection of a D1R selective agonist (chloro-APB hydrobromide) into the NAc notably reduced the time to emerge from propofol anesthesia with a decrease in δ-band power and an increase in β-band power evident in the cortical electroencephalogram. These effects were prevented by pretreatment with a D1R antagonist (SCH-23390). Whole-cell patch clamp recordings were performed to further explore the cellular mechanism underlying the modulation of D1 receptors on MSNs under propofol anesthesia. Our data primarily demonstrated that propofol increased the frequency and prolonged the decay time of spontaneous inhibitory postsynaptic currents (sIPSCs) and miniature IPSCs (mIPSCs) of MSNs expressing D1 receptors. A D1R agonist attenuated the effect of propofol on the frequency of sIPSCs and mIPSCs, and the effects of the agonist were eliminated by preapplication of SCH-23390. Collectively, these results indicate that modulation of the D1 receptor on the activity of NAc MSNs is vital for emergence from propofol-induced unconsciousness.